Pengembangan Flash Card untuk Meningkatkan Motivasi Belajar Ilmu Pengetahuan Sosial di SMP Bustanul Ulum - Zahroh, Faniatus; Mariatun, Ika Lis (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – At school, students often encounter various learning challenges, with a particular issue being their lack of motivation, which makes it difficult for them to absorb lessons. This research aims to investigate the procedures for developing Flash card learning media, assess its appropriateness, and identify the development of student learning motivation after the use of Flash cards in the Social Sciences subject, specifically the economic activity material, for class VII at Bustanul Ulum Islamic Junior High School.Method – The research method employed in this study is a type of Research and Development (R&D), specifically focusing on media research and development using the ADDIE model. ADDIE stands for Analysis, Design, Development, Implementation, and Evaluation. Data collection involves the use of questionnaires from media experts, material experts, field practitioners, and student responses. Data analysis techniques incorporate both qualitative and quantitative approaches.Findings – The findings indicate that Flash card media is suitable for application and can significantly impact students, particularly in Social Studies subjects. This is evidenced by validation results from media experts, linguists, field practitioners, and the improved student scores compared to previous assessments. Research Implications – The implications of this research demonstrate that the application of Flash card learning media can enhance students' learning motivation. This research specifically focuses on the economic activity material in class VII Social Studies. The scope of the research is limited to one school and a specific set of subjects.